Implanting multi-functional ionic liquids into MOF nodes for boosting CO2 cycloaddition under solventless and cocatalyst-free conditions - Chen, Yan; Li, Fangfang; Liu, Laiyao; Zhou, Ying-Hua (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•MIL-101(Cr) nodes were tethered by ionic liquids bearing hydrogen-bond donor.•MIL-101(Cr) derivative as catalyst boosted the epoxide cycloaddition with CO2.•The heterogeneous catalyst containing carboxyl displayed superior activity.•The catalyst exhibited the great durability and recyclability. It is critical to design an effective catalyst for CO2 conversion into cyclocarbonate to achieve the carbon neutrality. Herein, MIL-101(Cr) tethered by hydrogen bond donors (HBD)-containing ionic liquids (denoted as MIL-101-ILs(R), R = OH, NH2, and COOH) were synthesized through the implantation of 4,4′-bipyridine into MOF nodes via the post-synthetic modification, followed by the decoration with bromoalkanes including bromoethanol, bromoethylamine, and bromoacetic acid. Their catalytic performance were evaluated by the epoxide cycloaddition reaction under 1.0 MPa CO2 and 80 ℃ for 6 h in the absence of solvent and cocatalyst. Compared to MIL-101-ILs without HBD, MIL-101-ILs(OH) and MIL-101-ILs(NH2) demonstrated the more chloropropene carbonate (CPC) yield of 88 % and 83 %, respectively. Notably, MIL-101-ILs(COOH) exhibited an uppermost activity with a CPC yield of 96 %, attributed to the cooperativity of Lewis acidity originating from Cr3O clusters, hydrogen-bond interaction afforded by carboxyl groups, and the strong nucleophilicity offered by Br- ions of ILs. Moreover, MIL-101-ILs(COOH) presented excellent recyclability. A potential catalytic mechanism for epoxide cycloaddition with CO2 into cyclic carbonate has been proposed.